2012
DOI: 10.1063/1.4771125
|View full text |Cite
|
Sign up to set email alerts
|

Photoresponse from noble metal nanoparticles-multi walled carbon nanotube composites

Abstract: On the alternatives for bath correlators and spectral densities from mixed quantum-classical simulations J. Chem. Phys. 137, 224103 (2012) Inhibition of plasmonically enhanced interdot energy transfer in quantum dot solids via photo-oxidation J. Appl. Phys. 112, 104302 (2012) Highly efficient photochemical HCOOH production from CO2 and water using an inorganic system AIP Advances 2, 042160 (2012) Photoisomerization for a model protonated Schiff base in solution: Sloped/peaked conical intersection perspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 25 publications
2
13
0
Order By: Relevance
“…Notably, the first dynamics of MWCNTs decorated with Ag and Cu NPs results in greater intensity than the others. As reported in the literature [21], a static charge transfer from the NP to the CNT, caused by a not negligible difference in electronegativity between carbon and Cu, Ag, and Au, is present at the interface of the hybrid architecture. The presence of a static charge transfer permits us to have a larger availability of charges in the occupied states that increases the intensity of the signal.…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…Notably, the first dynamics of MWCNTs decorated with Ag and Cu NPs results in greater intensity than the others. As reported in the literature [21], a static charge transfer from the NP to the CNT, caused by a not negligible difference in electronegativity between carbon and Cu, Ag, and Au, is present at the interface of the hybrid architecture. The presence of a static charge transfer permits us to have a larger availability of charges in the occupied states that increases the intensity of the signal.…”
Section: Resultssupporting
confidence: 70%
“…In order to shed light on this second dynamics we have performed ab initio simulations, within the DFT in the LDA of the electronic structure at the CNT/ NP interface. Due to the large diameter of the CNTs, the curvature of the tube could be safely neglected so that the NP/CNT interface was simulated using a graphene layer with a metal NP on top of about 0.8 nm diameter [21]. The dielectric function of decorated and pristine graphene has been calculated within the independent single-particle approach (Fermi golden rule).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Going into details: i) the resonant interaction between the electromagnetic field of the incident light and the surface charge of metallic nanoparticles causes an electric field enhancement close to the nanoparticles which in turn gives rise to an increase of the light harvesting ability of the active layer around them; ii) the incident light can be reflected and scattered by the metal nanoparticles while passing through the active layer, thereby increasing its optical path length and improving its absorption probability. The ability of metallic (Au, Ag and Cu) nanoparticles to improve the EQE of carbon nanotube based photoelectrochemical solar cells was also demonstrated in other papers , Scarselli et al 2012b) but there interpreted in terms of charge transfer enhancing the total number of carriers. Photovoltaic properties of CNT-Si solar cells were also shown to be improved by including some graphene "patches" in the nanotube network (Li et al 2010a) or by exposing the nanotube surface to gas flow, thus lowering the CNT network sheet resistance (Fan et al 2012).…”
Section: Other Strategies To Improve Swcnt/si Device Performancesmentioning
confidence: 65%
“…Several groups have shown that the photoresponse in CNT-based photo-devices can be improved when the CNTs are functionalized with other nanostructures. In particular, they have been decorated with either semiconducting [8,82,83] or metal nanoparticles [84,85]. In the former case, the semiconducting material can be for instance TiO 2 or CdS.…”
Section: Carbon Nanotube-based Photo-sensorsmentioning
confidence: 99%